Text in multimedia - Abubakar, Adamu; Zeki, Akram M.; Bhatti, Zeeshan (IIUM Press, 2015)
Text refers to presentation of information aimed for establishing a communication between a writer and a reader. It is the most widely used and flexible means of communication. Text and symbols are the first way communication in the history of human civilization. It begins with meaningful marks which were scraped onto mud tablets and left to harden under the sun so that it can dry and become readable (Keechul et al., 2004). Even at the time, those that could be able to read needs to undertake some lessons.